2011
DOI: 10.3139/146.110508
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation strengthening in high manganese austenitic TWIP steels

Abstract: At low strains (e < 0.25), the precipitation of Ti, Nb, V carbides in austenitic Fe -Mn -C steels which exhibit twinning induced plasticity has no significant effect on work hardening. Strengthening follows the Orowan mechanism and can be described by a simple yield stress offset. However, at higher strains (e > 0.3) the work hardening rate decreased slightly. Synchrotron X-ray diffraction analysis suggested that this was due to a reduction in the kinetics of twin formation. The highest strengthening coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(93 citation statements)
references
References 25 publications
4
73
0
Order By: Relevance
“…Moreover, some large austenite grains also contain the deformation nanotwins (Figure 3(f)). The high thermal stability of deformation nanotwins in present medium Mn steel could be due to V-alloying as it can increase austenite recrystallization temperature [18].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some large austenite grains also contain the deformation nanotwins (Figure 3(f)). The high thermal stability of deformation nanotwins in present medium Mn steel could be due to V-alloying as it can increase austenite recrystallization temperature [18].…”
Section: Resultsmentioning
confidence: 99%
“…5) Microalloying elements such as Ti, Nb and V were deliberately added into Fe(1822)Mn(0.60.9)C TWIP steels to improve the YS by their carbide precipitation. 6) While the increments in YS with additions of Ti, Nb and V to TWIP steels were 1380, 187 and 530 MPa per weight percent, respectively, the strain hardening after yielding was not significantly influenced by the microalloying elements. 6) Considering the crucial effect of mechanical twinning on strain hardening behavior in TWIP steels, the kinetics of mechanical twinning seems to be insignificantly affected by the addition of microalloying elements.…”
Section: Introductionmentioning
confidence: 90%
“…19 Besides, twin boundaries can also enhance the workhardening rate by reducing dislocation mean free path. 19,[24][25][26][27] Experimental measurements [28][29][30][31] of the dislocation density by X-ray diffraction and line profile analysis reveal that the dislocation density of TWIP steels at fracture (with a true strain of 0?4-0?5) is usually in the order of 10 15 m…”
Section: Deformation Mechanismmentioning
confidence: 99%
“…28 The strengthening coefficients on yield stress of these microalloying elements as carbides are 1380 MPa wt-% 21 for Ti addition <0?1 wt-%, 187 MPa wt-% 21 for Nb and 530 MPa wt-% 21 for V addition <0?4 wt-% respectively. 28 Detailed TEM observation reveals that dislocations (either perfect or partial) can bypass these carbides according to the Orowan mechanism, indicating that the strengthening effect should depend on the average distance of the carbides. 70 Besides, it is also found that the nanometre sized deformation twins can bypass the carbides.…”
mentioning
confidence: 99%
See 1 more Smart Citation